Home-Based Computerized Cognitive Training for Postoperative Cognitive Dysfunction After Lung Transplantation in Elderly Population: A Randomized Controlled Trial. Issue 8 (August 2019) - Song, Yanping; Cui, Xueling; Zhang, Yan; Gao, Huiying; Cai, Qiaoying; Mu, Zhenzhen
Abstract : Abstract: Postoperative cognitive dysfunction is a severe outcome after lung transplantation, especially in the elderly lung transplant recipients. Home-based computerized cognitive training (CCT) is a widely used intervention for cognition improvement, but its efficacy has not been validated in this population. A randomized controlled trial was conducted to analyze the effect of CCT on elderly lung transplant recipients. The participants received either an 8-week CCT intervention or usual care. The changes of cognitive function were assessed between preintervention (T1), postintervention (T2), and 12 weeks postintervention (T3). Among the 46 participants, 91.3% completed the interventions. The CCT group performed better than the control group on Digit-Span Forward Test (T3: p = 0.0044) and Verbal Fluency Test (T3: p = 0.0331), indicating the efficacy of CCT on verbal memory in the elderly lung transplant recipients. Although varied impacts were observed on different cognitive domains, it seems promising to use CCT on the elderly population after lung transplantation.